Motivation to learn? An advanced exploratory study of learning motivation of Central-East European Business Students - Vitai, Zsuzsanna; Benke, Mariann (Marketing & Menedzsment, 2021)
THE AIM OF THE PAPER We used self-determination theory to examine the motivation of business school students in Hungary. The research aimed to clarify whether extrinsic or intrinsic motivation or both dominates learning intentions among these students. Although student motivation to learn has been studying extensively, there is an absence of research evidence using this framework in Central-Eastern European higher education. Given the increasing prominence of the region in global geo-political and business affairs, this absence of understanding is important to correct. METHODOLOGY Our questionnaire-based study shows a strong link between some forms of extrinsic motivation and intrinsic motivation, along with evidence for the coexistence of extrinsic and intrinsic motivators in the same person. We used a modified version of Vallerand et al. (1992-1993) motivation-survey the “Academic Motivation Scale AMSC-28”. We added 11 plus questions to the questionnaire. The empirical research was a confirmative study about self-determination theory. The methodology used was descriptive statistics, correspondence, and correlation analysis. The size of the sample was 471. The purpose of our study was to check if the theory of Deci and Ryan are valid on the students of a university in Central Europe. MOST IMPORTANT RESULTS The purpose of our study was to check how the theory of Deci and Ryan applies to the students of a university in Central Europe. The results of the research highlight that the students could have both intrinsic and extrinsic motivation at the same time and intrinsic motivation is not the only type of motivation that could lead to good performance in learning and other activities. RECOMMENDATIONS The findings could help to evaluate currently used motivational strategies for students and to stimulate further research on the subject usinűg the framework of self-determination theory. Acknowlwdgements: The authors would like to thank Professor John Schermerhorn and Professor Gábor Rappai for their valuable comments and critique in writing this article. With the support of the EFOP-3.6.3-VEKOP-16-2017-00007 project.